Loss of CHT3 in Candida albicans wild-type strains increases surface-exposed chitin and affects host-pathogen interaction - Blázquez-Muñoz, María Teresa; Costa-Barbosa, Augusto; Alvarado, María; Mendonça, Alexandre; Benkhellat, Sami; Vilanova, Manuel; Fernández-Sánchez, Sebastián; Correia, Alexandra; de Groot, Piet W. J.; Sampaio, Paula (Frontiers in Cellular and Infection Microbiology, 2025)
The chitinase Cht3 plays a major role in the chitinolytic activity of the pathogenic yeast Candida albicans and has also been proposed as a major antigen with potential for vaccine development against systemic candidiasis. The current study aims to enhance our knowledge on the role of Cht3 in cell surface organization and virulence of C. albicans. To this end, CHT3 deletion mutants generated in two wild-type genetic backgrounds (reference strain SC5314 and clinical isolate 124A) were phenotypically characterized. Absence of CHT3 did not affect growth rate but affected cell separation of dividing yeast cells at 37 °C. Further, cht3Δ mutants showed enhanced levels of surface-exposed chitin and slightly increased resistance to the cell wall perturbants Calcofluor white and Congo red and the β-1,3-glucan hydrolyzing enzyme Zymolyase, while the total level of chitin appeared unaltered. Deletion of one gene copy diminished CHT3 transcript levels by about 90% in both backgrounds. In strain 124A, showing two-fold higher CHT3 expression than SC5314, loss of CHT3 was compensated by upregulation of CHT2. Infection studies with cht3Δ mutants in strain 124A showed that CHT3 deletion led to attenuated virulence. Histological analysis of infected kidneys showed that CHT3 deletion did not affect the morphology of C. albicans cells during infection, but it appeared to delay activation of macrophages for efficient yeast killing. In conclusion, this study demonstrated that Cht3 activity is required for normal cell separation during yeast growth, cell surface organization, and full virulence of C. albicans in vivo. Its importance for virulence aligns with the earlier observed potential of Cht3 as vaccine candidate and warrants further studies to elucidate the mechanisms underlying its role in virulence and interaction with the host immune system.